A failure analysis study on the fractured connecting bolts of a filter press. (October 2015) - Molaei, Sh.; Alizadeh, R.; Attarian, M.; Jaferian, Y.
Highlights: Fatigue resulted in co-fracture of 16 connecting bolts of a filter press. It has been shown that proper torques were not used for tightening of the bolts. The bolts failed due to the separation between members. Abstract: The purpose of this study was to investigate the main causes of the co-fracture of sixteen connecting bolts of a filter press cylinder–piston system. Stress state of the bolts during the service conditions has been analyzed and the failure reasons were determined from the fractography analysis and gathered information. According to the obtained results, it was concluded that the bolts had failed by the fatigue mechanism. It seems that insufficient torque was used during assembly.